2012
DOI: 10.1002/bit.24522
|View full text |Cite
|
Sign up to set email alerts
|

Novel renewable ionic liquids as highly effective solvents for pretreatment of rice straw biomass by selective removal of lignin

Abstract: Cholinium amino acids ionic liquids ([Ch][AA] ILs), a novel type of bio-ILs that can easily be prepared from renewable biomaterials, were investigated for pretreatment of rice straw by selective extraction of lignin from this abundant lignocellulosic biomass material. Of the eight ILs examined, most were demonstrated to be excellent pretreatment solvents. Upon pretreatment using these ILs, the initial saccharification rates of rice straw residues were substantially improved as well as the extent to which polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
198
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(210 citation statements)
references
References 52 publications
11
198
1
Order By: Relevance
“…Carbohydrate losses are generally low and degradation products are significant only at severe conditions. Through the work of authors such as Cheng et al [193], Xie et al [172], Dadi et al [166], Hou et al [194], and others, it is known that significant sugar yields are achieved without the elimination of crystallinity.…”
Section: Applicationmentioning
confidence: 99%
“…Carbohydrate losses are generally low and degradation products are significant only at severe conditions. Through the work of authors such as Cheng et al [193], Xie et al [172], Dadi et al [166], Hou et al [194], and others, it is known that significant sugar yields are achieved without the elimination of crystallinity.…”
Section: Applicationmentioning
confidence: 99%
“…Cholinium ILs are a class of ILs that have low toxicity and are readily biodegradable. 48 Nockemann et al 49 demonstrated that the cholinium ILs, choline saccharinate and choline acesulfamate, can be prepared from easily available starting materials such as chicken feed additives (choline chloride) and artificial sweeteners (saccharinate and acesulfamate salts). In addition to biodegradability, the production of ILs from renewable materials is a very important consideration in a biorefinery and in this regard bio-based ILs have been prepared and tested for biomass pretreatment.…”
Section: Toxicity Biodegradability and Renewabilitymentioning
confidence: 99%
“…Extended contact time facilitates extraction of lignin (Tan et al 2009;Hou et al 2012). A longer contact period enhances the diffusion of ILs into the pores of the biomass matrix, resulting in improved dissolution and extraction of lignin (Tan and Lee 2012).…”
Section: Timementioning
confidence: 99%